2017
DOI: 10.1007/s13205-017-0768-8
|View full text |Cite
|
Sign up to set email alerts
|

Metabolite analysis of endophytic fungi from cultivars of Zingiber officinale Rosc. identifies myriad of bioactive compounds including tyrosol

Abstract: Endophytic fungi associated with rhizomes of four cultivars of Zingiber officinale were identified by molecular and morphological methods and evaluated for their activity against soft rot pathogen Pythium myriotylum and clinical pathogens. The volatile bioactive metabolites produced by these isolates were identified by GC-MS analysis of the fungal crude extracts. Understanding of the metabolites produced by endophytes is also important in the context of raw consumption of ginger as medicine and spice. A total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 52 publications
0
12
0
Order By: Relevance
“…Endophytic fungi isolated from four ginger cultivars ( Zingiber officinale ) were known to produce a myriad of bioactive fatty acids, one of which was oleic acid. It was assumed that a different composition of fatty acids among ginger cultivars was structured by native endophytic fungi ( Anisha and Radhakrishnan, 2017 ). Oleic acid along with linoleic acid and sciadonic acid were the shared components identified by GC-MS between lipid-producing endophytic fungus and its host, the Chinese Torreya grandis ( Yang et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Endophytic fungi isolated from four ginger cultivars ( Zingiber officinale ) were known to produce a myriad of bioactive fatty acids, one of which was oleic acid. It was assumed that a different composition of fatty acids among ginger cultivars was structured by native endophytic fungi ( Anisha and Radhakrishnan, 2017 ). Oleic acid along with linoleic acid and sciadonic acid were the shared components identified by GC-MS between lipid-producing endophytic fungus and its host, the Chinese Torreya grandis ( Yang et al.…”
Section: Discussionmentioning
confidence: 99%
“…Zingiberaceae is a medicinal plant family regularly used in traditional remedies and as herbal medicine, especially in Indonesia (Fernando and Nursyahra, 2008;Hartanto et al 2014;Juwita et al 2018). The associative endophytes have been reported from various sources leading to the progressive development of study and exploration of diverse endophytic fungi harbouring different habitats (Ginting et al 2013;Anisha and Radhakrishnan, 2017;Hastuti et al, 2008). A vast number of endophytic fungi in Zingiberaceaen species may also indicate an inter-relationship among the fungi within the plant tissue in the way of the co-synthesis of desired phytochemicals.…”
Section: Introductionmentioning
confidence: 99%
“…(Cimmino et al, 2017), Diaporthella cryptica (Cimmino et al, 2018). Moreover, several studies have also reported tyrosol from the bioactive extracts of endophytic Colletotrichum (Colletotrichum gleosporoides, Colletotrichum crassipes) (Anisha and Radhakrishnan, 2017;Masi et al, 2018;Plotnikov and Plotnikova, 2020). However, the report of its isolation from C. coccodes is limited.…”
Section: Discussionmentioning
confidence: 99%
“…However, the existence of endophytic fungi in the rhizome part of Zingiberaceae family may be different across members and cultivars. Different metabolite profiles of endophytic fungi were reported through the study of four Zingiber officinale cultivars collected from Rio de Janeiro and India, explaining varieties of host genotypes [34]. Assemblages of fungal community were also reported to be different among plant parts in one species.…”
Section: A Endophytic Fungi Isolates From Amomum Centrocephalum Rhizomementioning
confidence: 99%